Synthesis, Characterization and Antiinflammatory Activity of Chalcone Derivatives Linked with Apocynin and 5-Nitrofuran Moiety - Reddy, A.L.V. Kumar; Kathale, Niren E. (Asian Journal of Chemistry, 2017)
The present paper describes the synthesis of some new chalcone derivatives i.e. 1-[3-methoxy-4-(5-nitro-furan-2-ylmethoxy)-phenyl]-3-(substituted phenyl)-propenone derivatives (9A-9K) from furfural and apocynin as starting materials. Claisen-Schmidt reaction of 1-(4-((5-nitrofuran-2-yl)methoxy)-3-methoxyphenyl)ethanone (7) with aromatic aldehydes (8A-K) under solvent free conditions using solid NaOH as catalyst at room temperature resulted in the formation of chalcone derivatives (9A-9K) in 86-96 % yield. These compounds were characterized by 1H NMR, Mass and IR spectroscopy and were evaluated for their anti-inflammatory activity.